Process of validation of complex conceptual models after soft systems - Silva, J. (ICSB 2010 World Conference - Entrepreneurship: Bridging Global Boundaries, 2010)
A theoretically validated model to position a discussion about Production Planning and Control (PPC) within a rich organisational context was found as the main outcome of the process. Then, ten rival frameworks were described, as representing other systems thinking, to compare the conceptual model, by following the Soft Systems Methodology (SSM). Analysed dimensions concerned the gap, purpose, scope and expected results, research method, validation of results, models and outcomes and, conclusions. An appreciation of other researchers’ work was provided, promoting the improvement of PPC decision-making. In addition, guidance to operationalise stage 4b of SSM was presented. To sum up, science methods might help entrepreneurs to learn more robust processes to deal with complex corporate structuring, and so, to address some determinants of both organizational behaviour and effective management. In this way, corporations may be offered more credible vehicles for both intra- and entrepreneurship, providing safer bridges to jump over boundaries.